The game of developing a game : hobbyist game developers as playful entrepreneurs in the Apple App Store - Pietilä, Irmeli (Jyväskylä studies in business and economics, ISSN 1457-1986, 2015)
Yhteenveto (Finnish summary)
Keywords: pelit; peliteollisuus; yrittäjyys; yrittäjät; harrastajat; pelaajat; peliala; pelisuunnittelu; epävarmuus; toimeenpano; toteutus; riskit; verkkoyhteisöt; asiakkaat